Should we offer disaster preparedness and response training workshops across Idaho? A feasibility study - Iqbal, MD, FCPS, MPH, Meesha; Mashal, PhD, PE, Mustafa; Khan, MD, Muhammad Arslan; Grider, DO, John; Squires, BS, Rebecca; Richardson, BA, Ryan; Koudelka, MS, John A.; Thornley, MSN, ACNP-BC, Amy; van Woerden, PhD, Irene (Journal of Emergency Management, 2022)
Introduction: It is important for individuals and families to prepare for potential disasters to enable communities to generate a consolidated response. It is estimated that 30 percent of residents of the fourth largest city in Idaho, Idaho Falls, are not prepared to deal with disasters. A 1-day training workshop for healthcare professionals and students at Idaho State University in Pocatello was organized to build their capacity for acute disaster response and preparedness. This study assesses the impact of the workshop in improving knowledge and attitudes of the participants toward disaster management. Methods: A mixed methods study design was employed. Pre- and post-tests were administered to the participants (n = 18) to examine change in self-perceived understanding of disasters, and disaster preparedness and management. Core competencies encompassing knowledge of disaster preparedness were assessed via 18 multiple-choice questions. Participant attitudes toward disaster training exercises in colleges, universities, and healthcare facilities were recorded, and written feedback regarding the workshop obtained. Chi-square and paired t-tests were used to examine changes in disaster preparedness and cumulative knowledge score. Quantitative variables and comments were analyzed using Stata.v.13 and Maxqda, respectively. Results: Our assessment indicates an improvement in mean knowledge score [pretest: 10.7 (2.8), post-test: 12.5 (2.9); p = 0.007] and self-perceived disaster preparedness and management. The attitude of audience toward training workshops was wholly positive in both the pre- and post-tests. Participants commented that the workshop was “excellent,” helped them polish their knowledge and skills, trained them to build emergency kits and communication plans, and perform triage amidst crises. Conclusion: Training workshops should be offered to communities to build their capacity to prepare for and respond to disasters.